Pengaruh Project Based Learning Terhadap Kreativitas Mahasiswa dalam Mengembangkan APE berbasis Kewirausahaan : The Influence of Project Based Learning on Student Creativity in Developing Entrepreneurship-based APE - Asih Nur Ismiatun; Nyimas Muazzomi; Nurizati Syafina (IKIP Siliwangi, 2024)
Creativity is an important skill in accordance with 21st century learning which demands 4C skills. Every lesson is expected to apply an appropriate model, one of which is project based learning. The aim of this research is to determine the effect of implementing PjBL on student creativity in entrepreneurship-based educational games media development courses. This study is a one group pretest-postet experiment with the sample being 5th semester students of the early childhood education program, Jambi University. The data collection technique uses project assessment with the paired sample t-test analysis technique. The results showed that the 2-way significance value (t-tailed) was 0.00 <0.05. Therefore, it can be stated that the application of project based learning influences student creativity in developing entrepreneurship-based educational games tools.